2018
DOI: 10.1002/jso.25145
|View full text |Cite
|
Sign up to set email alerts
|

MR lymphography in patients with upper limb lymphedema: The GPS for feasibility and surgical planning for lympho‐venous bypass

Abstract: MR lymphangiography is an accurate and reproducible method for imaging and mapping of lymphatic channels in the lymphedemateous limb.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0
6

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 17 publications
0
33
0
6
Order By: Relevance
“…Preoperative MRL allowed the identification of 7.2 ± 2.4 submental lymph nodes, which was greater than preoperative ultrasound doppler (3.2 ± 1.1) and intraoperative finding (3.1 ± 0.6) (Asuncion et al, 2018). Zeltzer et al (2018) conducted a prospective on 25 patients with upper extremity lymphedema where MRL allowed the identification of lymphatic circulation in 18 patients. They reported that LVA was successfully performed in 16 patients from their cohort (Zeltzer et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Preoperative MRL allowed the identification of 7.2 ± 2.4 submental lymph nodes, which was greater than preoperative ultrasound doppler (3.2 ± 1.1) and intraoperative finding (3.1 ± 0.6) (Asuncion et al, 2018). Zeltzer et al (2018) conducted a prospective on 25 patients with upper extremity lymphedema where MRL allowed the identification of lymphatic circulation in 18 patients. They reported that LVA was successfully performed in 16 patients from their cohort (Zeltzer et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…Zeltzer et al (2018) conducted a prospective on 25 patients with upper extremity lymphedema where MRL allowed the identification of lymphatic circulation in 18 patients. They reported that LVA was successfully performed in 16 patients from their cohort (Zeltzer et al, 2018). Lohrmann et al (2008) used MRL to preoperatively and postoperatively (LVA or Lymph vessel transplant) evaluate lymphedema grade and lymphatic channel characteristics.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…So wurde ein schweres Lymphödem in 46 % der Patienten mit aplastischen, 37 % der Patienten mit hyperplastischen, aber nur bei 15 % der Patienten mit hypoplastischen und nie bei Patienten mit normalen inguinalen Lymphgefäßen beobachtet [20]. [20,22]. Es sind also insbesondere die neueren Operationsmethoden, die zur adäquaten Therapieplanung eine exakte Diagnosestellung sowie eine möglichst genaue Lokalisierung funktioneller (!)…”
Section: Klinische Anwendungenunclassified
“…Lymphgefäße und -knoten erfordern. Die präoperative Darstellung einzelner Lymphgefäße sowie deren anatomische Lagebeziehung zu venösen Gefäßen ist in der MRL ohne weiteres möglich und kann auch gelingen, wenn mittels ICG-L keine Gefäße darstellbar sind [22]. Darüber hinaus kann die MRL auch zur postoperativen Verlaufsbeurteilung und zur Beurteilung möglicher Komplikationen eingesetzt werden.…”
Section: Klinische Anwendungenunclassified